2014
DOI: 10.1016/j.schres.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on cognitive endophenotypes in schizophrenia

Abstract: Background Cognitive deficits are prominent in schizophrenia and represent promising endophenotypes for genetic research. Methods The current study investigated the importance of two conceptually distinct genetic aggregates, one based on copy number variations (uncommon deletion burden), and one based on single nucleotide polymorphisms identified in recent risk studies (genetic risk score). The impact of these genetic factors, and their interaction, was examined on cognitive endophenotypes defined by princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Cognitive decline with the age, both in the normal aging and in the pathological manifestations in form of dementia, is an important public health and social challenge. Individual variability of cognitive functions is an important endophenotype of many neurodegenerative, psychiatric, and mental diseases, such as schizophrenia (SZ) [ 1 ], Alzheimer's diseases (AD) [ 2 ], bipolar disorder [ 3 ], and attention-deficit hyperactivity disorder [ 4 ]. Recent genome-wide association studies (GWAS) have revealed dozens of single nucleotide polymorphisms (SNPs) associated with a cognitive performance in SZ or AD patients, as well as in normal healthy subjects [ 5 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive decline with the age, both in the normal aging and in the pathological manifestations in form of dementia, is an important public health and social challenge. Individual variability of cognitive functions is an important endophenotype of many neurodegenerative, psychiatric, and mental diseases, such as schizophrenia (SZ) [ 1 ], Alzheimer's diseases (AD) [ 2 ], bipolar disorder [ 3 ], and attention-deficit hyperactivity disorder [ 4 ]. Recent genome-wide association studies (GWAS) have revealed dozens of single nucleotide polymorphisms (SNPs) associated with a cognitive performance in SZ or AD patients, as well as in normal healthy subjects [ 5 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One approach that has recently generated progress regarding our understanding of the pathophysiology of psychiatric disorders is that of intermediate phenotypes (also described as endophenotypes) (Erk et al, 2013;Insel and Cuthbert, 2009;Yeo et al, 2014). Advances in functional and structural brain MRI have provided alternative methods for studying core phenotypes that may be more proximal to genetic contributions and that may underlie psychiatric illness (Hariri et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In the Philadelphia neurodevelopmental cohort, investigators also found schizophrenia PRS associations for speed of emotion identification, an aspect of social cognition ( Germine et al, 2016 ). Earlier studies utilizing genetic risk scores did not find associations with cognitive domains ( Yeo et al, 2014 ) or IQ in schizophrenia ( Van Scheltinga et al, 2013 ), though the lack of association could be explained by smaller sample sizes.…”
Section: Introductionmentioning
confidence: 85%